Perancangan Sistem Informasi Pengajuan Kredit Kendaraan Bermotor (Studi Kasus : FIF Group Kedaton Bandar Lampung) - Dodi Afriansyah; Didik Kurniawan (Universitas Mitra Indonesia, 2021)
AbstractOne type of vehicle that is in great demand by the public is a motorized vehicle. Motorized vehicle is any vehicle that is driven by mechanical equipment in the form of a machine other than a vehicle that runs on rails. In the past, motorbikes were a type of vehicle that was quite expensive but over time, now motorbikes are not a type of vehicle that is difficult to own. This is due to the presence of a motorcycle loan program held by the leasing party, one of which is the FIF Group. FIF Group is one of the financing or leasing companies in Indonesia that has motor vehicle credit facilities. Currently, FIF GROUP is still in the process of applying for credit using the conventional method, namely by coming directly to the dealer or via WhatsApp for data requirements. In addition, the credit application process is too time-consuming and expensive. Based on this, the researcher proposes an information system for applying for a motor vehicle loan based on a website. From the results of the analysis and testing, the application made can be used to apply for a motorcycle loan and runs according to the original purpose of this study. In addition, the application of this motorized vehicle information system can save time and costs, because the application created has a centralized data source.